Efektivitas Guided Imagery Terhadap Penurunan Tekanan Darah Pada Hipertensi - Herliana, Irma; Solehudin, Solehudin (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2024)
The phenomenon of hypertension in society is a serious and quite common health problem. Unhealthy lifestyles, such as a diet high in salt, lack of physical activity, excessive alcohol consumption, and smoking, can increase the risk of hypertension. The aim of this community service activity is to increase public knowledge in managing blood pressure using Guided Imagery therapy. Community Service Activities in the form of Health Education with the theme "Efforts to Lower Blood Pressure in Hypertension". Counseling will be held in Kebon Raya Bogor on December 6 2023 at 10.00 – 12.00 WIB. Community service activities in the form of health education involve nursing professional students along with community nursing clinical practice activities. After being given counseling, the level of public knowledge about hypertension and its treatment using Guided Imagery increased by 29.5%. Meanwhile, the average blood pressure decreased by 10 mmHg after Guided Imagery was carried out. Guided Imagery can be useful in lowering blood pressure in individuals with hypertension through several mechanisms that have the potential to reduce stress and improve the body's response to stress.